PENGARUH KARAKTERISTIK DEWAN KOMISARIS, KARAKTERISTIK PERUSAHAAN DAN PENGENDALIAN EKSTERNAL TERHADAP KEBERADAAN RISK MANAGEMENT COMMITTEE - Desi Waty Febryna (Jurnal Akuntansi Bisnis, 2015)
The inherent risks in firmsoperating activities require firms to establish effective risk management. The complexity of modern bussiness forces firms to put more effors to reduce negative effects of uncontrolled risks. Risks management is becoming crucial Risk Management Committee has been widely established in many public firms. This committee is under the supervision of Board of Commissioners. This study examine the effects of Corporate Governance, the characteristics of the company and auditor quality on the existence of Risk Management Committee of non-financial public companies. This study uses secondary data from annual reports of non-financial companies listed on Indonesia Stock Exchange in 2008-2013. Using logistic regression, the results show that frequency of board meetings, concentration of ownership and size of the company affects the existence of the Risk Management Committee (RMC).